Identifikasi dan Karakterisasi Bakteri Kontaminan melalui Uji Biokimia sebagai Upaya Evaluasi Keamanan Produk Obat, Pangan, Kosmetik dan Lingkungan - Christica Ilsanna Surbakti; Manahan Situmorang; Reza Fikrih Utama; Viera Nazlia; Yosi Yunisa Gaja (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Bacterial contamination in pharmaceutical, food, cosmetic, and environmental products poses a significant global health challenge. This study aims to identify and characterize bacterial contaminants through biochemical testing approaches to evaluate the safety of various product types. Methods employed include bacterial isolation, Gram staining, and a series of conventional biochemical tests such as carbohydrate fermentation, catalase, oxidase, IMViC, and TSIA. A systematic review of 15 scientific journals across multiple disciplines revealed that the most frequently identified contaminants were Staphylococcus aureus, Escherichia coli, Salmonella sp., Bacillus sp., Pseudomonas aeruginosa, and Enterobacter sp. These findings were consistently detected across diverse matrices, including fishery products, traditional foods, cosmetics, dairy milk, landfill soils, and indoor air of shopping centers. The study concludes that biochemical testing remains a reliable and cost-effective method for preliminary identification of bacterial contaminants across various sectors. However, confirmation using molecular methods such as PCR and 16S rRNA sequencing is strongly recommended to improve identification accuracy. Stricter safety standards and consistent hygiene practices are essential throughout the production chain of pharmaceutical, food, and cosmetic products to protect public health.